Роль експерта в проведенні комплексної судово-психолого-психіатричної експертизи в сучасній Україні - Макарова, О. П.; Makarova, O. P. (Соціологія права. - 2023. - Вип. 1-2. - С. 60-63, 2023)
Запропонована стаття розглядає місце комплексної судово – психолого – психіатричної експертизи в умовах сучасного Українського законодавства. Розглядається роль експерта-психолога та експерта-психіатра при проведенні комплексної експертизи. Визначаються перспективи щодо розширення практики застосування комплексної судово-психолого-психіатричної експертизи в цивільних та кримінально – процесуальних процесах.

Possibilities and achievements of psychiatry can be used to a great extent in modern judicial proceedings in both quantitative and qualitative terms: quantitatively – thanks to the expansion of the scope of understanding, qualitatively – in the aspect of improving complex forensic psychological and psychiatric examination. The main types of forensic examinations conducted by an expert include forensic psychological and complex forensic psychological and psychiatric examinations. The development of psychological examination began in the second half of the 20th century, and a little later complex forensic psychological and psychiatric examination emerged. Currently, the number of comprehensive forensic psychological and psychiatric examinations conducted in Ukraine exceeds the number of homogeneous forensic psychological or forensic psychiatric examinations. This may be due to the solutions to issues related to the use of special psychological knowledge, when the judicial and investigative bodies have some doubts about the mental capacity of the person undergoing expert examination, and this, in turn, is the basis for conducting an examination using special psychiatric knowledge. The appointment and conducting of a complex forensic psychological and psychiatric examination has practical advantages for judicial investigative bodies, because instead of conducting two types of forensic psychological and forensic psychiatric examinations, one complex forensic psychological and psychiatric examination is performed, which in turn significantly increases cost-effectiveness of examination proceedings and shortens investigative periods. When conducting a complex forensic psychological and psychiatric examination, a wide range of additional paraclinical studies can be used to substantiate the clinical diagnosis, if necessary, specialists are involved for the examination of sub-experts, namely: biochemists, medical psychologists, neuropathologists, etc. Considering the role of an expert – a psychologist, we note that he provides only advisory assistance to an expert psychiatrist for the correct solution of diagnostic and expert issues that are related only to the competence of forensic psychiatry. For this purpose, an experimental-psychological study of the cognitive processes of the sub-expert is conducted, based on the results of which a written conclusion is drawn up. Such cooperation helps the expert psychiatrist to more accurately establish a medical diagnosis and provide answers to questions that have arisen in judicial and investigative bodies. The proposed article examines the place of complex judicial-psychological-psychiatric examination in the conditions of modern Ukrainian legislation. The role of an expert-psychologist and an expert-psychiatrist in conducting a comprehensive examination is considered. Prospects for the expansion of the practice of the application of complex forensic psychological and psychiatric examination in civil and criminal procedural processes are determined.

Предлагаемая статья рассматривает место комплексной судебно – психолого – психиатрической экспертизы в условиях современного Украинского законодательства. Рассматривается роль эксперта-психолога и эксперта-психиатра в проведении комплексной экспертизы. Определяются перспективы расширения практики применения комплексной судебно-психолого-психиатрической экспертизы в гражданских и уголовно процессуальных процессах.
The role of the expert in the conduct of a complex forensic-psychological-psychiatric examination in the judiciary of Ukraine
Keywords: експерт; expert; эксперт; судово-психологічна експертиза; forensic psychological examination; судебно-психологическая экспертиза; комплексна судово – психолого-психіатрична експертиза; complex forensic - psychological and psychiatric examination; комплексная судебно – психолого-психиатрическая экспертиза